The Morning After : Explaining the Slowdown in Japanese Growth in the 1990's - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 1999)
This paper uses vector autoregressions (VARs) to investigate four explanations of the extended slump in Japanese economic activity during the 1990s: the absence of bold and consistent fiscal stimulus; limited room for expansionary monetary policy because of a liquidity trap; asset price deflation reflecting the long-term problems caused by overinvestment, inadequate returns on saving, and debt overhang; and disruption of financial intermediation. The results indicate that disruption in financial intermediation, largely operating through the impact of changes in domestic asset prices on bank lending, has been the principal case of the slump.